Human Energy/ edited by Ashok V. Desai - "Desai, Ashok V. (ed.)" (New Delhi, 1990)
At the end of the United Nations Conference on New and Renewable Sources of Energy held in Nairobi, Kenya, in August 1981, the then Prime Minister of Canada, the Right Honourable Pierre Elliott Trudeau, announced an additional CAD 10 million for the International Development Research Centre (IDRC) to expand its support for energy research.
Keywords: Economics